Introduction to Islamic banking and finance an economic analysis - Hassan, Kabir; Shaikh, Salman Ahmed; Kayhan, Selim (World Scientific, 2020)
This book, Introduction to Islamic Banking and Finance, will cover the basic principles of Islamic economics and finance. It will discuss both the theory of Islamic economics and finance as well as the applications in the design of instruments of finance as well as Islamic financial institutions. It will enable the readers to gain an understanding of the structures and operations of Islamic banking, Islamic capital market investments, risk management and accounting for Islamic banking contracts. The book sets forth the following objectives: To get an overview of the principles of Islamic economics and understand their contrast with mainstream economics. To get an overview of basic rules of commercial law in Islamic jurisprudence. To get an overview of basic principles, structures and operations of Islamic banking both in the liability side and asset side operations. To gain an understanding of Islamic capital market instruments and investment management including some unique activities peculiar to Islamic investments, such as stock screening and income purification. To understand the different Takaful structures, which are applied for risk management by individuals and corporates.